2018
DOI: 10.1080/10790268.2018.1533316
|View full text |Cite
|
Sign up to set email alerts
|

Dry needling technique decreases spasticity and improves general functioning in incomplete spinal cord injury: A case report

Abstract: Context: Spasticity in neurological disorders (i.e. stroke patients and cerebral palsy) is positively improved by dry needling. However, reports are scarce regarding the potential effects of dry needling in reducing spasticity and improving functionality in patients with an incomplete spinal cord injury. The aim of this case report was to study the immediate, short-term effects of dry needling treatment (10 weeks) on spasticity, dynamic stability, walking velocity, self-independence, and pain in a single patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Because we did not have literature to support our choice for an efficacious dose of IMES in people with MS, we used parameters based on clinical judgement and previous studies in other neurological populations. 7 , 12 15 Another limitation of the study was that we could not attribute changes we observed in spasticity to IMES, TM + FES, or a combination of these interventions. Additionally, this study might be subject to selection bias, as many of the participants were able to walk longer distances.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because we did not have literature to support our choice for an efficacious dose of IMES in people with MS, we used parameters based on clinical judgement and previous studies in other neurological populations. 7 , 12 15 Another limitation of the study was that we could not attribute changes we observed in spasticity to IMES, TM + FES, or a combination of these interventions. Additionally, this study might be subject to selection bias, as many of the participants were able to walk longer distances.…”
Section: Discussionmentioning
confidence: 99%
“…While other studies have investigated the short-term effects of dry needling/IMES for the treatment of spasticity in individuals with stroke and spinal cord injury, our study is novel in that it used a two-pronged approach to address spasticity and gait impairments in individuals with MS. 7,[12][13][14][15] Slowed gait speed has been associated with fall risk in people with MS, 28 and the T25FW is often used to measure gait speed in this population as it is highly correlated with falls. 29 Coleman and associates suggest a 20% decrease in time in the T25FW constitutes a minimal clinically important difference (MCID).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dry needling is an invasive procedure that consists of reaching muscle myofascial trigger points (MTPs) with a needle [38]. MTPs are small, tense muscle nodules that cause pain, cause weakness, and limit range of motion [39].…”
Section: Dry Needlingmentioning
confidence: 99%